EFEKTIFITAS PEMANFAATAN MEDIA TANGRAM TERHADAP KONSEP BANGUN DATAR PADA SISWA MI - Dina Nurkhakiki, Ade; Abu Jihad, Fadhil; Sabillah, Miftah; Fitri Hasanah, Anggi; Sulistyani, Anjar (Trigonometri: Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Mathematics education at the elementary level, especially in flat geometric material, often faces challenges in terms of understanding abstract concepts. One alternative to overcome this is to use interactive learning media, such as tangram. The purpose of this study is to evaluate how well Madrasah Ibtidaiyah (MI) uses tangram media to teach plane geometry. Tangram, which takes the form of a geometric puzzle, can help students understand the nature of flat shapes and practice spatial thinking and fine motor skills. Apart from that, the use of tangram can also stimulate students' creativity, imagination and critical thinking skills through a fun and challenging learning process. Based on a literature review, the use of tangrams has proven effective in increasing students' interest in learning, deepening understanding of geometric concepts, and helping students, including those with special needs, in recognizing and categorizing various geometric shapes. It is hoped that this research can provide recommendations to educators to utilize tangram media in mathematics learning, so that it can contribute to improving the quality of basic education, especially in the field of mathematics. Keywords: learning media, tangram, flat shapes, geometry, mathematics learning, madrasah ibtidaiyah, spatial thinking skills, creativity, understanding concepts, basic education